Hubungan Sikap Pustakawan terhadap Tata Ruang Kerja di Dinas Perpustakaan dan Kearsipan Kota Padang - Lubis, Fitria Nurhaliza; Erlianti, Gustina (ALSYS, 2024)
This study aims to determine; 1) what is the work space layout in the Padang City Library and Archives Service; 2) what is the attitude of librarians at the Padang City Library and Archives Service; 3) what is the relationship between librarians' attitudes towards work space layout in the Padang City Library and Archives Service. This research uses a quantitative descriptive method. The population of this research was 15 librarians with a sample of 15 respondents. Sampling used a saturated sampling technique. The main instrument of this research is a questionnaire. The instrument tests used are validity tests and reliability tests. Test the analysis requirements using the Spearman rank correlation test, hypothesis test and coefficient of determination test. The research results show that the results of the Spearman Rank correlation analysis show that the correlation between work space layout and librarian attitudes is 0.744. With a correlation value of 0.744, if seen from the table, this figure is in the interval 0.60 – 0.799 with a strong level of relationship. Based on the correlation coefficient hypothesis test, it can be seen that the value of Fcount (13.075) > Ftable (5.14) means there is a relationship between the work space layout variable and the librarian attitude variable. The results of this research found that the higher the work space layout in the library, the higher the quality of the librarian's attitude in working in the library.